A corpus-based grammar of spoken Pite Saami - Wilbur, Joshua (Christian-Albrechts-Universität zu Kiel, 2013)
A description of the phonology and grammar of the Pite Saami (Uralic, Sweden) language based on a documented corpus of the contemporary spoken language Eine Beschreibung der Phonologie und Grammatik des Pitesaamischen (Uralisch, Schweden) basierend auf einem dokumentierten Korpus der gegenwärtigen gesprochenen Sprache